2008
DOI: 10.1007/s00432-008-0473-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on relationship between angiogenesis and micrometastases of peripheral blood in breast cancer

Abstract: MVD count and positive expression of VEGF-A closely correlated to hMAM mRNA released from tumor cells in the circulation. hMAM mRNA is expected to become a valuable marker for further study on micrometastases of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In this study, we demonstrated that Nes + MVD in IDC was higher in patients with lymph node metastases than in cases without lymph node invasion. Similar results for MVD, but for different endothelial antigens (i.e., CD31 and CD34) were obtained by Weidner et al (6), Popiela et al (35) and Xie et al (36). Furthermore, we demonstrated that Nes + MVD increases with the histological grade of IDC and achieves the highest value in the G3 and the lowest in G1 tumours.…”
Section: Univariate Cox Analysis Multivariate Cox Analysis P-value Hrsupporting
confidence: 91%
“…In this study, we demonstrated that Nes + MVD in IDC was higher in patients with lymph node metastases than in cases without lymph node invasion. Similar results for MVD, but for different endothelial antigens (i.e., CD31 and CD34) were obtained by Weidner et al (6), Popiela et al (35) and Xie et al (36). Furthermore, we demonstrated that Nes + MVD increases with the histological grade of IDC and achieves the highest value in the G3 and the lowest in G1 tumours.…”
Section: Univariate Cox Analysis Multivariate Cox Analysis P-value Hrsupporting
confidence: 91%
“…The method most commonly used to assess angiogenesis is immunohistologic analysis of the mean intratumoral microvascular density (MVD), which is a valuable prognostic indicator for a wide range of tumor types and is well corrected with increased metastasis and patient mortality (17)(18)(19). Studies in animal tumor models demonstrate that the treatment with antiangiogenic agents is associated with a decrease in MVD ( 20,21 ).…”
Section: Animal Modelmentioning
confidence: 99%
“…In a study of 50 invasive ductal carcinomas, expressions of VEGFA protein and mRNA were correlated with tumor size, lymph node metastasis and TNM staging. The MVD counts were correlated with the expression of VEGFA and axillary lymph node metastasis [43]. Cox analysis revealed that intratumoral VEGFA was an independent prognostic factor for node-negative breast cancer [44].…”
Section: Roles Of Vegfa In Breast Cancermentioning
confidence: 99%